Microstructure Evolution in a β-γ TiAl Alloy during Hot Deformation under Variable Conditions - Guoju Li; Zhanxing Chen; Yupeng Wang; Xinzhe Zhang; Qiuwei Xing; Xinfang Zhang; Chunyuan Yuan; Tengfei Ma (Crystals, 2023)
In contrast to practical hot compression processes, the testing of the hot workability of TiAl alloys is usually conducted under the conditions of constant strain rates and constant temperatures. This work aims at investigating the microstructural evolution of TiAl alloys on a Gleeble-3800 thermomechanical simulator under a variable strain rate (0.1, 0.01 and 0.001 s−1) at 1200 °C. The results show that, after a holding time of 30 s, the abrupt change in the strain rate at ε = 0.3 (engineering strain) has a remarkable influence on the flow stress and dynamic recrystallization (DRX) behavior of the β-γ Ti-44Al-6Nb-1Mo-0.3 (B, Y, La, Ce) (at.%) alloy. The flow stress demonstrates a rapid decrease with a sudden reduction in the strain rate. A duplex microstructure of γ + B2/β can be obtained under a high strain rate or continuous medium strain rate. During the two-step deformation, however, both γ→α phase transformation and DRX exist, and the content of the α phase demonstrates a significant increase when the strain rate becomes lower. Finally, a fine-grained structure of γ + B2/β + α2 phases with low residual stresses can be obtained via the two-step heat treatment processes. This provides a promising approach to significantly improve the hot workability of β-γ TiAl alloys.